Microbial load in septic and aseptic procedure rooms: results from a prospective, comparative observational study - Kramer, Axel; Harnoß, Julian-Camill; Kohlmann, Thomas (Deutsches Ärzteblatt, 2017)
We thank Prof. Büttner-Janz for her contribution. As she rightly says, microbial load in partial results in our study was tendentially higher after septic procedures than after aseptic ones (1). Because of the wide spread and the very small...